"…instead of spending two hours in books, I’m discussing with my guy…": Students’ perspectives on their academic performance in a Ugandan nursing school. - Lyagoba, Ivan; Okusa, John Micheal; Asekenye , Irene (Student's Journal of Health Research Africa, 2025)
Background Nurses and midwives constitute 50% of the global health workforce, yet critical shortages, especially in sub-Saharan Africa, limit healthcare delivery. Uganda reports one of the lowest staffing levels globally, with rural districts like Pallisa severely affected. While several educational enablers and barriers have been documented elsewhere, limited evidence exists locally. This study aimed to explore nursing and midwifery students’ perceptions of factors influencing their academic performance in Pallisa. Methods This was a qualitative, explorative study that employed focus group discussions (FGDs) with 28 certificate-level nursing and midwifery students at AAMSNM, stratified by year of study. Four FGDs were conducted, and data were collected using a semi-structured interview guide. Audio recordings were transcribed, coded, and analyzed thematically to identify institutional, teacher-related, and student-related factors influencing academic performance. Results Students identified a range of barriers to academic performance, including limited access to skills labs, power outages, strict institutional policies, and overlapping academic schedules. Teacher-related challenges such as fast-paced instruction, incomplete syllabus coverage, and lack of guidance were commonly reported. Personal factors like poor time management, exam-related stress, smartphone and romantic distractions, and inadequate preparation also emerged as critical issues. Positive contributors to academic success included peer group discussions, tutor engagement via WhatsApp, clinical exposure, and supportive administrative adjustments such as flexible exam policies and access to Wi-Fi. Conclusion Academic performance among nursing students is shaped by multifactorial challenges, many of which are modifiable. Addressing institutional constraints, enhancing teacher-student interaction, and promoting student-centered academic support systems can significantly improve student outcomes. Peer collaboration, structured exam preparation, and emotional support mechanisms are also vital in fostering success. Recommendations Academic institutions need to invest in mentorship, digital learning tools, and flexible academic structures to support students’ academic and emotional well-being.